Analysis of a hybrid control scheme in the district heating system with distributed variable speed pumps. (July 2019) - Gu, Jihao; Wang, Jin; Qi, Chengying; Yu, Xiaojuan; Sundén, Bengt
Highlights: Hybrid control scheme has a great advantage in reducing pressure in pipelines. Distributed variable speed pumps have a relative error of 7.71%. Distributed variable speed pumps improve hydraulic stability of the primary network. Distributed variable speed pumps save 28.52% power consumption than without. Abstract: Compared with conventional central circulating pumps (CCCPs) in the district heating system (DHS), the DHS with distributed variable speed pumps (DVSPs) shows a great potential for energy saving. In this paper, a hybrid control scheme both using electric control valves (ECVs) and DVSPs is applied to the district heating system in Shenyang, China. This new hybrid control system results in reduction of the boiler outlet pressure from 1.27 MPa to 0.81 MPa, which ensures safe operation of the heating network. In addition, the hydraulic imbalance of the primary pipelines is effectively reduced by using the DVSPs. It is found that the relative error between the designed and the measured total flow rates is 7.71%. Results show that the annual average value of electricity consumption by using the DVSPs is 28.52% smaller than that in the CCCP system. Therefore, there is a great potential for building energy saving if the DVSPs are installed into the DHS. In order to evaluate the heating quantity and guide the optimal operation for the DHS, indoor temperature acquisition devices will be installed in the near future.